Material flow analysis and human resources allocation regarding heavy weight lifting: A case study from a gas bottle preparation unit - Porto, Leonardo Rocha (2017)
Dissertação de Mestrado em Engenharia e Gestão Industrial apresentada à Faculdade de Ciências e Tecnologia